ANALISIS HURUF INNA WA AKHWATUHA DAN. METODE PEMBELAJARANNYA DALAM AL-QURAN SURAT AD-DUKHON: INNA WA AKHWATUHA DALAM AL-QURAN SURAT AD-DUKHON - Langgeng Sutopo (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
This journal is entitled Inna Wa Akhwatuha in Al-Quran Surat Ad-Dukhon. The author chose this title because some people do not really understand the letter inna wa akhwatuha, and some of them are still confused by the translation and form of harokat inna wa akhwatuha. Inna wa akhwatuha is amil which serves to strengthen the mubtada' and the khobar. Isim and khabar of inna wa akhwatuha are very diverse, as is widely available in Al-Quran Surah Ad-Dukhon. Isim inna wa akhwatuha is in the form of zhohir or dhomir, and there is usually a form of mufrod, number, even number of shibh. In this surah, there are many arrangements of inna wa akhwatuha, approximately 28 sentences along with the isim and the khobar which some of Arabic learners find it difficult to distinguish between the types of isim and khobar but only know the deeds of inna wa akhwatuha. The formulation of the problem in this study are (1) What are the types of isim inna wa akhwatuha found in the Al-Quran Surat Ad-Dukhon? (2) What are the types of khobar of inna wa akhwatuha found in the Al-Quran Ad-Dukhon? While the purpose of this study is (1) To find out and describe the types of isim inna wa akhwatuha contained in the Al-Quran Surat Ad-Dukhon. (2) to describe the type of khobar inna wa akhwatuha contained in the Al-Quran Surat Ad-Dukhon. This research is a qualitative study. Researcher used library research design or often referred to as library research. The data in this study are isim and khobar inna wa akhwatuha in Al-Quran Surat Ad-Dukhon. The results of this study are to increase understanding of inna wa akwatuha and understand the interpretation of Surah Dukhon which is full of wisdom and learning in it.